Who Am I discovering the self-concept across the lifespan - Dy, Marison R. (Philippine Journal of Counseling Psychology, 2006)
This study explored the various dimensions and self-representations of the self-concept across the lifespan. In addition, it also looked into how individuals define their self-concepts in terms of accuracy of assessment, consistency/stability and positivity-negativity. The 100 respondents from Los Baños, Laguna, aged 8-82 years old, were each administered an interview schedule to look into the mentioned variables. Specifically, the findings of the study were: (1) the dimensions which were highly reflected in the respondents' statements were the social and personality dimensions with the physical dimension also reflected in the children's statements, the cognitive dimension reflected in the adolescents' statements, and the spiritual dimension reflected in the adults' statements; (2) that the "ideal selves" of the respondents were based on their dream professions, being happy, successful and of service to others; the "ought selves" were based on their dream professions, being good, serving others and playing their family roles well; the "could selves" were related to their dream professions, family roles, being good and of service to others; and the "afraid-to-be selves" of the respondents were about being bad people, sickly and useless, and being failures in life; (3) that 83.3% of the respondents received validation for their reported statements about their self-concepts; (4) that traits, both positive and negative, were generally reported as remaining consistent in the self-concept although children also included behaviors and appearance; adolescents included values; early adults included principles and faith in God; middle-aged adults included values/principles and abilities; and the elderly included faith in God; and (5) that the respondents, generally look at themselves positively with the elderly showing greater positivity of the self-concept.